MyTapauFoodie: enhancing food delivery service and helping the poor by leveraging on network-of-restaurants and network-of-mosques capabilities - Ahmad Dahlan, Abdul Rahman; Sulaiman, Muhammad Hasif; Che Mohamad Nor, Auzaie; Razak, Nurul E'zzati (Eclat Research Publication, 2017)
This project is made for customers targeting market in Malaysia in order to provide them with food delivery service that allow food to be delivered easily and quickly from selected food vendors. The proposed project also will enable users to co-operate with the Network-of-Halal-Restaurants and Network-of-Mosques (NOM) in helping the society by encouraging customers to donate money to buy food for the needy.